Nuclear forms of superoxide dismutase, catalase and peroxidase - Protas, A. F. (Биополимеры и клетка, 1996)
Nuclei of rat brain cortex cells contain ownspecific forms of superoxide dismutase (SOD), catalase (CAT) and gluthatione peroxidase (GPx). The enzymes are firmly associated with chromatin, preferationally with transcriptionally active fraction and released from nuclei completely with >1.2 M Nad. Mr of SOD is 10 kDa, CAT and GP× 44 kDa (gel-filtration). Isoelectric points of SOD is under pH 6.0, CAT and GPx 5.8 ( chromatofocusing). The activities of enzymes depend on ionic strength and are maximal under >1.1 MNaCl. Nuclear SOD are not inhibited with KCNand thus, it is MnSOD. Ядра клітин кори головного мозку щурів містять власні специфічні форми супероксиддисмутази (СОД), калатази (КАТ) і глутатіонпероксидази (ГПер). Ферменти міцно асоційовані з хроматином (переважно з транскрипційно активною фракцією) та екстрагуються при концентрації NaCl > 1,2 М, СОД має Мг 10 к Да, КАТ і ГПер – 44 к Да (гель-фільтрація); ізоелектричну точку зафіксовано для СОД при рН 6,0, для КАТ і ГПер – при рН 5,8 (хроматофокусування). Активність ферментів залежить від іонної сили і стає максимальною при концентрації NaCl > 1,1 М. Ядерна СО Дне пригнічується KCN і, мабуть, є МпСОД Ядра клеток коры головного мозга крыс содержат собственные специфические формы супероксиддисмутазы (СОД), каталазы (КАТ) и глутатионпероксидазы (ГПер). Ферменты прочно ассоциированы с хроматином (преимущественно с транскрипционно активной фракцией) и экстрагируются при концентрации NaCl> 1,2 М. СОД имеет Мг 1G кДа7 КАТ иГПе44 кДа (гель-филыпрация); изоэлектрическая точка для СОД зафиксирована при рН 6,0, для КАТ и ГПер – 5,8 (хроматофокусирование). Активность ферментов зависит от ионной силы и максимальна при концентрации NaCl >1,1 М. Ядерная СОД не ингибируется KCN и, видимо, представляет собой МпСОД